(untitled) (Papeles, 2023)
This work aims to become a contribution that accounts for the beginnings of a social intervention procedure that is on its way to completing 150 years, in 2025, of existence in Argentina: the home visit. For this, a qualitative research is carried out based on the use of two primary sources and various secondary sources. In the case of the former, the document of the municipal ordinance that regulates home visits and the initial reports of the municipal inspectors of the City of Buenos Aires constitute original contributions on the subject. This documentation is analyzed and interpreted through theoretical reflections that arise from the contributions of other investigations, located in a revisionist perspective of our history, more focused on the particularities of the processes. In this sense, and as an example, the participation of women is considered in the passage from the domestic space to the public rather than in a static and residual place of charity, and the aspects related to the subject-environment relationship are placed in their characteristics of condition and possibility, in conflict with the perspective of deterministic genetic inheritance. In the year 1875 the municipal government of Buenos Aires regulated it in a context of public control actions of the nascent "modern state" and the emergence of the "early social question". Liberal and reformist thought deploys its knowledge and practices within the framework of the positivist current of thought. So that? to access the daily life of others, to the private/domestic space; to regulate the conflicts between biology and culture. The figure of the "inspector" will be consolidated as the authorized knowledge for this task, enabled by recent municipal regulations